The Participation of The Indigenous Women’s Association in The Recovery of Cultural Tourism in Bali, Indonesia - Ni Ketut Sari Adnyani; I Gusti Ayu Purnamawati (Jurnal Manajemen Perhotelan, 2024)
This research aims to determine the impact of technology transfer, cultural change, and feminist participation in the development of cultural tourism. The research method used is field research with the sampling technique used is random sampling and data collection techniques through document study, observation and interviews. Conducted in cultural tourism villages in Bali Province with a sample of 8 districts and 1 municipality. The research results show that technological transfer and cultural changes do not have a significant effect on the recovery of cultural tourism. On the other hand, participation has a significant effect on tourism recovery. Recovery of cultural tourism in this research; the emphasis is on the growth of tourist villages in cultural tourism. Culture forms the local wisdom of tourist villages which must be preserved and passed down from generation to generation. The participation of indigenous feminists as workers in tourist villages also supports the preservation of religious tourism, customs, culture and traditions in realizing the restoration of Balinese cultural tourism. Cultural changes and the transfer of technology have also changed the mindset of the Balinese traditional community, which was originally steeped in a patriarchal culture to become gender-responsive.